2022
DOI: 10.3390/diagnostics12102344
|View full text |Cite
|
Sign up to set email alerts
|

Could Chronic Rhinosinusitis Increase the Risk of Ulcerative Colitis? A Nationwide Cohort Study

Abstract: Chronic rhinosinusitis (CRS) is a common chronic inflammatory disease of the sinonasal mucosa with an inflammatory or infectious etiology. Inflammatory bowel disease (IBD) causes chronic intestinal inflammation. Thus, both diseases share innate immune and epithelial barrier dysfunctions of the mucosa. However, the association between sinusitis and IBD is not well-known. We aimed to determine the association between CRS and the risk for IBDs, such as Crohn’s disease (CD) and ulcerative colitis (UC). In this lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Besides, Lin et al found that patients with IBD history, especially UC, had an increased risk of subsequent development of CRS [16] . A 10-year-long retrospective cohort study by Lee et al including 15,175 CRS patients and 30,350 controls to assess the subsequent incidence of IBD, shown that CRS was signi cantly related to the risk of UC(adjusted HR = 1.72, 95% CI = 1.26-2.36) after adjusting for sex, age, residence, income level, and comorbidities, but not CD, and more precisely, the subgroup analysis shown that CRS without nasal polyps was related to an increased incidence of UC(adjusted HR = 1.71, 95% CI = 1.24-2.35) [15] . However, not all observational studies have found a correlation between CRS and IBD [17,28] .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Besides, Lin et al found that patients with IBD history, especially UC, had an increased risk of subsequent development of CRS [16] . A 10-year-long retrospective cohort study by Lee et al including 15,175 CRS patients and 30,350 controls to assess the subsequent incidence of IBD, shown that CRS was signi cantly related to the risk of UC(adjusted HR = 1.72, 95% CI = 1.26-2.36) after adjusting for sex, age, residence, income level, and comorbidities, but not CD, and more precisely, the subgroup analysis shown that CRS without nasal polyps was related to an increased incidence of UC(adjusted HR = 1.71, 95% CI = 1.24-2.35) [15] . However, not all observational studies have found a correlation between CRS and IBD [17,28] .…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it is worthy of further studying the relationship between CRS and IBD. Actually, there are several studies having already evaluated the relationship between CRS and IBD [14][15][16][17] , but the results are inconsistent. However, it is noteworthy that these evidence come only from observational studies, which are hard to infer causality and avoid the impact of confounding factors [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Third, depending on the design of this study, it is unknown whether our findings indicate a causal relationship between the two diseases or a simple temporal association between them. However, despite these limitations, several previous studies examining the relative association between the two diseases have used the same cohort dataset as ours [49][50][51][52]. Further clinical and experimental studies are required to confirm the possible link between these two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, this nationwide population-based dataset allowed us to identify the total medical service history; hence, we could assess the association between psychological comorbidities and the risk of BMS while adjusting for clinical and demographic factors. Numerous retrospective cohort studies have already published similar study designs using this database [ 28 , 29 , 30 , 31 , 32 , 33 ]. Moreover, we selected patients with BMS diagnosed by otorhinolaryngologists to improve diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%